PELATIHAN DAN PENDAMPINGAN PEMBUATAN MEDIA AJAR INOVATIF DI KELAS RENDAH MI PLUS AL-FALAH SUNGAI LULUT BANJARMASIN TIMUR - Tutus Rani Arifa; Jumiati Jumiati; Sari Kumala; Muhammad Iqbal Ansari (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
MI Plus Al Falah Sungai Lulut East Banjarmasin School, which was established in 2020, is one of the first private schools around the Lulut river area, East Banjarmasin, in the learning system there has never been any assistance for educators in introducing the creation of innovative teaching media. Guidebooks and student worksheets or can be called (LKS) as a guide in the ongoing learning process. In the stages of introduction to writing, reading, speaking and listening, students still introduce the lecture model. Innovative teaching media can be applied from educators to students how educators introduce letters, numbers, addition, subtraction, limbs in humans, types of animals that are adapted to their habitats and there are many discussions of material adapted to the thematic syllabus. Training and mentoring in the creation of innovative teaching media (posters, interactive boards/books, props, songs, videos, games, technology-based tools). The solution offered is by providing training and assistance in making innovative teaching media from materials that can be reached by both educators and students such as (styrofoam, used cardboard, markers, origami paper, cardboard, flannel, glue, straws, drink bottles and so on). etc.) can be used as an innovative teaching medium in the lower classes. With the aim of improving teacher competencies, especially those related to the ability to design, implement learning processes and authentically assess each lesson at MI Plus Al-Falah Sungai Lulut East Banjarmasin. The method used in this service begins with lectures, discussions and questions and answers followed by demonstrations/practices, workshops/training and mentoring and finally evaluation. The output target to be achieved is an accredited journal